EFFECT OF ADS AND QUALITY OF PRODUCTS ON DECISION OF PURCHASING FRISIAN FLAG PRODUCT IN MEDAN CITY - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The company must be aware that in the era of globalization, advertising and product quality is an important factor to achieve success. Where advertising and product quality can affect consumers to buy goods and services companies at that time they need. To meet the needs and provide satisfaction, the company promotes through advertising, and has a good product quality in the hope that consumers decide to buy products offered.The purpose of this research is to know the influence of advertisement and product quality to purchase decision of Frisian Flag milk in Medan City. Sampling technique in this research use Acidental Sampling. The samples taken as many as 100 respondents who buy Frisian Flag products in the city of Medan. Data collection techniques with questionnaires distributed.The results of this study using Multiple Linear Regression where the most influential independent variables on the purchase decision of Frisian Flag milk in Medan City is the variable value of product quality (X2) of 0.685.To test hypothesis in this research, the researcher use t test (partial test), result of t test (partial test) influence of advertisement to decision obtained t arithmetic (2,904) > t table (1,66) this show there is an influence of advertisement significant for purchasing decision while the influence of product quality to purchase decision obtained t arithmetic (10,997) > t table (1.66) This shows there is influence of product quality to purchasing decision. Besides, F test (simultaneous) where the value of F arithmetic (83,635) > F table (3.09) this shows there is a significant influence of advertisement and product quality together to purchase decision. After that, the test of determination and obtained by the number 0.633 or 63.3%, which means that the relationship between advertising and product quality to purchase decision is strong.